STRATEGI KOMUNIKASI DIGITAL MELALUI INSTAGRAM @robotickidz DALAM PROMOSI LES PRIVAT DI ROBOTICKIDZ BOGOR - Rahmi, Eziza; Sartika, Ika (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2025)
ABSTRACT This study explores digital communication strategies via Instagram to promote private tutoring at RoboticKidz Bogor. It emphasizes the importance of digital promotion for non formal education institutions like RoboticKidz. The problem addressed is the lack of exposure to institution’s strengths. The objective is to evaluate the digital promotion strategy using the AIDA framework (Attention, Interest, Desire, Action). The study adopts a descriptive qualitative method through interviews and observations.Results show Instagram is effective in capturing attention and prompting action from potential customers. Conclusion: The AIDA strategy builds audience engagement and increases interest in educational services. Keywords: Digital Strategy, Instagram, Private Tutoring, Promotional Media, Social Media